(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Physical education (PE) plays a crucial role in the development of students’ physical fitness, motor skills, and overall well-being. However, traditional methods often fail to engage students effectively. This study explores the implementation of interactive simulators in secondary school PE programs to enhance student participation, motivation, and physical performance. The findings suggest that interactive simulators provide a dynamic and immersive experience that fosters an active lifestyle among students.